2016
DOI: 10.1242/bio.016527
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous optimisation of earwig hindwings for flight and folding

Abstract: Earwig wings are highly foldable structures that lack internal muscles. The behaviour and shape changes of the wings during flight are yet unknown. We assume that they meet a great structural challenge to control the occurring deformations and prevent the wing from collapsing. At the folding structures especially, the wing could easily yield to the pressure. Detailed microscopy studies reveal adaptions in the structure and material which are not relevant for folding purposes. The wing is parted into two struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
(56 reference statements)
0
21
0
Order By: Relevance
“…The occurrence of resilin in several broadened vein patches as well as in membranous folding lines was described for fan-like dermapteran hind wings [22,92]. These structures help folding the wing into a wing package being ten times smaller than the unfolded wing.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of resilin in several broadened vein patches as well as in membranous folding lines was described for fan-like dermapteran hind wings [22,92]. These structures help folding the wing into a wing package being ten times smaller than the unfolded wing.…”
Section: Reviewmentioning
confidence: 99%
“…Both unfolding mechanisms are supported by several wing stiffening mechanisms such as the mid-wing mechanism and the claval flexion line, which keep the wing unfolded in all species examined [22,93]. These mechanisms were found to play an important role both in the static unfolded state of the wing and during flapping flight, in which they help to inhibit an unfavorable folding of the wing [92]. Furthermore, the flexible resilin-bearing folding lines were found to not only serve wing folding but also act as flexion lines at which the wing flexes during flight, thereby supporting the generation of an aerodynamically favourable cambered wing profile [92,94].…”
Section: Reviewmentioning
confidence: 99%
“…It is believed that an insect is an excellent biological object for the bio-inspirations to de-sign and develop a MAV. For example, it has been found that the wings of some insects, such as Dermaptera, Coleoptera and Blattaria, become smaller by various folding ways to protect and maintain the functionality on ground meanwhile to provide the necessary aerodynamics for flight [2][3][4][5][6] . It is believed that if the similar mechanism of insect wings' folding is mimicked, MAVs' wings are foldable and their performances can be considerably enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…Once insects gained the ability to withdraw the wings upon their body, multiple ways to decrease the area of the stored wings repeatedly evolved. Earwigs fold their hind wings once fanwise and twice axially, reaching packing areas up to about 1/15 of the original wing surface ( 2 , 3 ). This extreme compactness allows these insects to fully flex their abdomen, enabling them to use their forcepslike cerci ( 4 ) and wriggle into narrow spaces, including digging in the soil ( 5 , 6 ), while usually maintaining fully functional flight capability ( 2 , 7 ).…”
mentioning
confidence: 99%
“…Earwigs fold their hind wings once fanwise and twice axially, reaching packing areas up to about 1/15 of the original wing surface ( 2 , 3 ). This extreme compactness allows these insects to fully flex their abdomen, enabling them to use their forcepslike cerci ( 4 ) and wriggle into narrow spaces, including digging in the soil ( 5 , 6 ), while usually maintaining fully functional flight capability ( 2 , 7 ). Unlike the patterns that typically occur in other insects that can fold their wings axially, such as most beetles ( 8 11 ), some cockroaches ( 12 ), and a few wasps ( 13 , 14 ), true bugs ( 15 ) and moths ( 16 ), the crease pattern of the earwig wing is conservative across the whole group and likely evolved only once ( 17 ).…”
mentioning
confidence: 99%